Propriedades magneto-óticas e de magneto-transporte de um diodo de tunelamento ressonante contendo Si δ - doping no poço quântico - Herval, Leonilson Kiyoshi Sato de (2011)
In this work, we have studied the transport and optical properties of GaAs = AlGaAs resonant tunneling diodes with Si delta-doping at the center of the quantum well. We have studied magneto-transport and polarized resolved photoluminescence from GaAs quantum well and contact layers as a function of applied voltage and magnetic _eld parallel to the tunnel current. Three resonant peaks are observed in the current-voltage characteristics curve and are associated to the resonant tunneling through the bound state of a shallow donor impurity in the quantum well (donor-assisted resonant tunneling), the electron resonant tunneling through the _rst con_ned state in the quantum well and the phonon-assisted tunneling. The contact layer and the quantum well emissions were investigated as a function of applied bias at 15 T. The optical emission from GaAs contact layers shows evidence of highly spin polarized two-dimensional electron (2DEG) and hole (2DHG) gases which a_ects the spin polarization of carriers in the QW. The quantum well (QW) photoluminescence presents strong circular polarization with values up to 85% in 15 T at low applied voltages (at the donor assisted resonant tunneling condition) and for low laser intensities. Our results may be interesting for the developing of new voltage-controlled spintronics devices.